Diet overlap among three sympatric African annual killifish species Nothobranchius spp. from Mozambique - Polacik, M; Reichard, M (Journal of fish biology, 2010)
The diet patterns of three Nothobranchius species (N. furzeri, N. orthonotus and N. rachovii), small, short-lived annual killifish from temporary pools in African savannah were investigated. Four sites with contrasting fish density and water surface area were sampled in 2008 and 2009 in southern Mozambique. Stomach content analysis showed that all the species examined were generalists, with diets largely based on aquatic invertebrates. The same invertebrate prey categories were consumed by all three species, but their relative proportions varied across species. The largest species, N. orthonotus, showed the most distinct diet and consumed vertebrates (juvenile lungfish Protopterus annectens and larval Amphibia) and a relatively high proportion of Odonata, Coleoptera and Ephemeroptera larvae. The diet of the other two species (N. furzeri and N. rachovii) showed a stronger overlap, did not include vertebrates, but was rich in small crustaceans (Cladocera, Copepoda, Ostracoda and Conchostraca). Mosquito (Diptera) larvae formed only a negligible part of the diet of all the three species.
Keywords: Animals; Fundulidae; stravovací zvyklosti; dieta; Mozambique; Mosambik; bezobratlí; zvířata; Diet; Feeding Behavior; Invertebrates